O museu como espaço educativo de um patrimônio cultural em movimento: estudo de caso Paço do Frevo - (:unkn) unknown (Universidade Federal do Pampa, 2025)
This study aims to analyze how the educational projects developed at the Paço do Frevo promote the cultural practice of frevo, integrating formal, informal and non-formal education. The research is based on the understanding that frevo, as an intangible cultural heritage, represents a fundamental element of Pernambuco’s and Brazil’s cultural identity. Using a qualitative approach and the content analysis method, an interview was conducted with an educator from the Paço do Frevo in order to understand the educational practices, methodologies, and the impacts of these actions on society and formal education. The results show that the activities carried out at the Paço do Frevo, as a space for the training and safeguarding of this heritage, combine culture, memory, and education. Its initiatives, such as workshops, courses, and thematic mediations, enable experiential learning and foster a sense of belonging. The dialogue with schools and the creation of new educational projects highlight the integration between formal and non-formal education. Moreover, the educational practices promote the appreciation of diversity and cultural identity, reinforcing the role of frevo as a historical heritage in constant movement. Thus, the Paço do Frevo stands out as an example of an institution that uses culture as an instrument of social and educational transformation.
The museum as an educational space for a cultural heritage in motion: a case study of Paço do Frevo
Keywords: Educação patrimonial; Frevo; Cultura; Educação não formal; Heritage education; Culture; Non-formal education; CIENCIAS SOCIAIS APLICADAS